2010
DOI: 10.4103/0019-5413.62084
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle morphometry in patients with adolescent idiopathic scoliosis

Abstract: Background:The key to the safe and effective use of thoracic pedicle screws in the deformed spine is to thoroughly understand pedicle anatomy. There are a few studies related to pedicle anatomy in the Indian population and no pedicle morphometric studies in scoliosis patients. The present study aims to highlight the differential features of pedicle morphometry, including pedicle width, transverse pedicle angle and the depth to anterior cortex on the concave and convex side, in a group of Indian patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 21 publications
(49 reference statements)
3
16
0
4
Order By: Relevance
“…Pedicle width measurements reported by Liljenqvist et al [17] were almost similar to the results of our study whereas Upendra et al [19] surprisingly showed wider pedicles almost throughout the curve. In several levels, data on pedicle width reported by Liljenqvist et al [17] showed smaller pedicles than our data.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Pedicle width measurements reported by Liljenqvist et al [17] were almost similar to the results of our study whereas Upendra et al [19] surprisingly showed wider pedicles almost throughout the curve. In several levels, data on pedicle width reported by Liljenqvist et al [17] showed smaller pedicles than our data.…”
Section: Discussionsupporting
confidence: 92%
“…Small pedicles at the concave side of the scoliotic apex have also been shown by two previous studies [17,19]. Pedicle width measurements reported by Liljenqvist et al [17] were almost similar to the results of our study whereas Upendra et al [19] surprisingly showed wider pedicles almost throughout the curve.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although newly developed imaging navigation techniques can assist in improving pedicle screw placement, failure to select appropriate screw size, screw starting point, and screw trajectory can result in pedicle screw misplacement which potentially can cause serious neurologic, vascular, or visceral injury [9,10,12,29,32]. There have been numerous studies examining the morphologic features of the pedicle and placement of pedicle screws in normal and adolescent idiopathic scoliosis spines using various definitions and measuring modalities [18,25,30,31,35,36]. The majority of these studies have identified clear size asymmetry in the pedicle widths between the concave and convex sides of the curve.…”
Section: Introductionmentioning
confidence: 99%